PENINGKATAN KETERAMPILAN GENERIK SISWA MELALUI PENERAPAN MODEL LEARNING CYCLE 5E DALAM PEMBELAJARAN IPA FISIKA KELAS VIII MTsN SUNGAI TONANG - Yosi Nofelia; Zulhelmi Zulhelmi; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aims to determine the increasing in student’s generic skill through the implementation of Learning Cycle 5E model in physics science learning process at grade VIII MtsN Sungai Tonang. The population of this research is class VIII consisting of 2 classes. Samples taken are 2 classes, determination technique experimental class and control class are by simple random sampling. This research was conducted in MTsN Sungai Tonang from July to December 2015. The design of this research was a True Experimental with Posttest-Only Control Design. Instrument of collecting data in this research is achievement test generic skill which given after learning. Data were analyzed by descriptive and inferential. Descriptive analysis of student’s generic skill after learning with implementation of Learning Cycle 5E model is 76,02% including the category of well. The results of inferential analysis obtained by value thitung > ttabel ( 4,015 > 2,028 ) , so we can conclude there is a significant difference to the generic skill applying Learning Cycle 5E model with a class that implements conventional teaching with a 95% confidence level . From both of the analysis, it can be concluded that implementation of Learning Cycle 5E model effective to improve student’s generic skill physics science learning process at grade VIII MTsN Sungai Tonang.Key Words: Generic Skill, Learning Cycle 5E, Force and Acceleration2